2013
DOI: 10.1103/physrevlett.110.266101
|View full text |Cite
|
Sign up to set email alerts
|

Spin Resolution and Evidence for Superexchange on NiO(001) Observed by Force Microscopy

Abstract: The spin order of the nickel oxide (001) surface is resolved, employing noncontact atomic force microscopy at 4.4 K using bulk Fe and SmCo tips mounted on a qPlus sensor that oscillates at sub-50 pm amplitudes. The spin-dependent signal is hardly detectable with Fe tips. In contrast, SmCo tips yield a height contrast of 1.35 pm for Ni ions with opposite spins. SmCo tips even show a small height contrast on the O atoms of 0.5 pm within the 2×1 spin unit cell, pointing to the observation of superexchange. We att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…2F were thought to originate from a single atom tip oriented in a [111] direction. We found that COFI images of Fe with its bodycentered-cubic (bcc) structure are similar to COFI images of tungsten (also bcc) [see figure S4 in (39)]. It is easier to evaporate Fe on Cu(111) than W because of its lower melting point.…”
mentioning
confidence: 69%
“…2F were thought to originate from a single atom tip oriented in a [111] direction. We found that COFI images of Fe with its bodycentered-cubic (bcc) structure are similar to COFI images of tungsten (also bcc) [see figure S4 in (39)]. It is easier to evaporate Fe on Cu(111) than W because of its lower melting point.…”
mentioning
confidence: 69%
“…Therefore, it is important to explore the full nature of electron-electron interaction, i.e., both the dipole coupling and the exchange coupling, when the NVC is placed in close proximity to the FHM. Recently, the exchange interaction between the ferromagnetic tip and the magnetic sample has also been considered in magnetic exchange force microscopy (MExFM) [42][43][44]. However, to the best of our knowledge, the exchange interaction between proximal NVC spins and FMH spins, has not been considered in NV-based magnetometry.…”
Section: Introductionmentioning
confidence: 99%
“…Applying a similar approach to the spin measurement of individual paramagnetic point defects has been proposed [6,7], yet after more than two decades since the first single-spin detection experiments [8], the spatial resolution of various electrical [9][10][11] , optical [12] and even scanning probe based single spin detection techniques [13][14][15] is one to two orders of magnitude above the localization of the paramagnetic states [8,9,11,13,14]. This limitation makes the application of these spin measurement techniques for a selective readout of adjacent paramagnetic states difficultor, as recently demonstrated, they are based on either scanning tunneling microscopy (STM) [15], spinpolarized scanning tunneling microscopy [16,17] or magnetic exchange force microscopy [17,18,19], all of which employ conductive probe tips, with free carriers that could limit spin coherence times of qubits when the spin readout is used for quantum information applications.…”
Section: Introductionmentioning
confidence: 99%